Indoor Channel Measurement at 300 GHz and Comparison of Signal Propagation With 60 GHz - Minseok Kim; Anirban Ghosh; Riku Takahashi; Kosuke Shibata (IEEE Access, 2023)
In this paper, a newly developed 300 GHz channel sounder is presented followed by a detailed description of test measurements and the subsequent results obtained to validate its working. An elucidation of the high-resolution double-directional channel measurement in a typical conference room scenario precedes the comparison of the results obtained for the current campaign to that obtained from an earlier campaign at 60 GHz for a similar setup. It is observed that a similar number of clusters for both the bands under investigation for all the transmitter (Tx) and receiver (Rx) positions are obtained from the generated power spectra. Any deviation is theorized to be caused either due to the usage of lower measurement bandwidth in the 60 GHz campaign or due to limited elevation expanse in the 300 GHz measurement. To identify the interacting objects (IOs) causing the clusters, environment-embedded angular power spectra (APS) and ray tracing simulations are used. The large-scale parameters (LSPs) are also evaluated for both campaigns. It is observed that signal propagation at 300 GHz is dominated more by the line-of-sight (LoS) path compared to 60 GHz. The results are also compared with other similar results from the literature.